'Invisible' orthodontics by polymeric 'clear' aligners molded on 3D-printed personalized dental models. (4th February 2022) - Yu, Xiaoye; Li, Guanghui; Zheng, Yikan; Gao, Jingming; Fu, Ye; Wang, Qunsong; Huang, Lei; Pan, Xiaogang; Ding, Jiandong
Abstract: The malalignment of teeth is treated classically by metal braces with alloy wires, which has an unfavorable influence on the patients appearance during the treatment. With the development of digitization, computer simulation and three-dimensional (3D) printing technology, herein, a modern treatment was tried using clear polymeric aligners, which were fabricated by molding polyurethane films via thermoforming on the 3D-printed personalized dental models. The key parameters of photocurable 3D printing of dental models and the mechanical properties of the clear aligner film material were examined. The precision of a 3D-printed dental model mainly relied on characteristics of photocurable resin, the resolution of light source and the exposure condition, which determined the eventual shape of the molded clear aligner and thus the orthodontic treatment efficacy. The biocompatibility of the polyurethane film material was confirmed through cytotoxicity and hemolysis tests in vitro . Following a series of 3D-printed personalized dental models and finite element analysis to predict and plan the fabrication and orthodontic processes, corresponding clear aligners were fabricated and applied in animal experiments, which proved the efficacy and biocompatibility in vivo . Clinical treatments of 120 orthodontic cases were finally carried out with success, which highlights the advantage of the clear aligners as an esthetic, compatible and efficient appliance.